Active protection scheme based on high‐frequency current for distribution networks with inverter‐interfaced distributed generators - Haifeng Li; Huamin Liang; Zhidong Wang; Zhenggang Zhang; Yuansheng Liang (IET Renewable Power Generation)
Abstract With the high penetration and flexible access of inverter‐interfaced distributed generators (IIDGs), it is gradually becoming difficult for traditional protection schemes to meet the requirements for the safe operation of distribution networks (DNs). Active protection schemes based on power electronic equipment provide a new approach. On the basis of the controllability of voltage source converters, a method for active high‐frequency signal injection and a selection principle for the corresponding control parameters are proposed. Considering the impact of T‐connected load branches on the protected line, the high‐frequency current characteristics at the three terminals during internal and external faults are analysed. On this basis, an active protection scheme based on high‐frequency current is proposed for DNs with IIDGs. The performance of the proposed scheme is verified via PSCAD/EMTDC simulation software. The test results show that the proposed scheme can reliably trip during internal faults and identify faulty phases, which has better endurance to fault resistance.